2017
DOI: 10.5800/gt-2017-8-3-0309
|View full text |Cite
|
Sign up to set email alerts
|

Meso-Neoproterozoic Grenville-Sveconorwegian intracontinental orogen: history, tectonics, geodynamics

Abstract: Abstract:The objective of this paper is to represent the main features inherent to Grenville-Sveconorwegian Orogen (GSNO) and to propose a model of tectonic and geodynamic evolution of this orogen based on the results of research concerning similar Precambrian tectonic units in the East European Craton. The studies of the conditions and settings related to origin and evolution of GSNO are of special interest, because it is located geographicaly and in a certain sense ideologically in the center of Rodinia, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 95 publications
(147 reference statements)
0
3
0
1
Order By: Relevance
“…3. Свеконорвежский [Bingen et al, 2021;Mints, 2017] и Свекофеннский [Daly et al, 2006] выступы кристаллических пород, для которых характерен циркон с возрастом около 1.0 и 1.6-1.8 млрд лет соответственно. Вместе с тем породы, содержащие циркон протерозойского возраста, также известны для комплексов, в настоящее время слагающих фундамент Тимано-Печорского региона и локально обнажающихся в районе Тиманского кряжа [Pystin et al, 2020, и ссылки в данной работе].…”
Section: комплексыunclassified
“…3. Свеконорвежский [Bingen et al, 2021;Mints, 2017] и Свекофеннский [Daly et al, 2006] выступы кристаллических пород, для которых характерен циркон с возрастом около 1.0 и 1.6-1.8 млрд лет соответственно. Вместе с тем породы, содержащие циркон протерозойского возраста, также известны для комплексов, в настоящее время слагающих фундамент Тимано-Печорского региона и локально обнажающихся в районе Тиманского кряжа [Pystin et al, 2020, и ссылки в данной работе].…”
Section: комплексыunclassified
“…14. Реконструкция палеопротерозойской эволюции Лавроскандии (Лавро-Русский внутриконтинентальный овальный коллизионный ороген): (а)~2.5 млрд лет, (б)~1.8 млрд лет (по [Mints, 2017a], с небольшими изменениями).…”
Section: неоархейская тектонометаморфическая зональность северо-америunclassified
“…Fig. 14. Reconstruction of the Paleoproterozoic evolution of Lauroscandia (Lauro-Russian intracontinental oval collisional orogen) (modified after [Mints, 2017a]). Ages: (а) -~2.5 Ga, (б) -~1.8 Ga.…”
Section: неоархейская тектонометаморфическая зональность северо-америmentioning
confidence: 99%
“…At the same time, considering the presence of numerous rounded and subrounded grains of this age (Fig. 3), which suggests their repeated reworking (Pettijohn, 1975), they could have been sourced from older sedimentary rocks, particularly those exposed within the Sveconorwegian-Grenvillian Orogen in the northern and northwestern (in the present-day coordinates) sectors of Baltica (Bingen et al, 2008;Mints, 2017;Rivers et al, 2012;Spencer et al, 2015;etc. ).…”
mentioning
confidence: 97%
“…The zircons with crystallization ages ranging from 1370 to 1170 Ma were supplied from another source, because rock complexes of this age are virtually absent in the structures of the basement of Baltica (Bogdanova et al, 2008;Lahtinen, 2012;etc.). At the same time, igneous and metamorphic events in the interval of 1.0-1.4 Ga are widely manifested within the Sveconorwegian-Grenvillian Orogen (including the terranes amalgamated within it), located in the northwestern (in the present-day coordinates) sector of Baltica (Bingen et al, 2008;Mints, 2017;Rivers et al, 2012;Spencer et al, 2015;etc.). An earlier U-Th-Pb dating of detrital zircons from the Upper Riphean sandstones of the Dzhezhimskaya Formation in the Southern Timan (Kuznetsov et al, 2010) demonstrated the prevalence of Early Proterozoic and Late Archean grains; at the same time, the studied population contained ~7% of grains with ages from 1350 to 1200 Ma.…”
mentioning
confidence: 99%